2022
DOI: 10.1371/journal.pone.0264082
|View full text |Cite
|
Sign up to set email alerts
|

External debt and economic growth in Sub-Saharan Africa: Does governance matter?

Abstract: This study empirically examined the impact of external debt on economic growth. Also, the interactions of governance, external debt and external debt volatility were further investigated with emphasize on the interective effect of governance as proxied by Kaufmann, D., (2007) quality governance measures such as; government effectiveness, political stability, voice and accountability, regulatory quality and corruption control on economic growth. The study utilized annual time series data, focusing on thirty sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 58 publications
3
18
2
1
Order By: Relevance
“…These findings corroborate the debt overhang hypothesis that an indebted country will find it difficult to undertake future investment projects since returns from any future investment would be diverted to the creditor in the form of promised payments (debt servicing) thereby creating a disincentive to invest and hence poor growth and development. The results of this study are also in tandem with the findings of previous empirical studies (Adubofour Isaac et al, 2021;Asteriou et al, 2021;Bal & Rath, 2014;Fejzaj et al, 2021;Fosu, 1996;Law et al, 2021;Le & Phan, 2022;Maitra, 2019;Makun, 2021;Manasseh et al, 2022;Pegkas, 2018) in which external debt stock and total external debt services were found to have significant adverse effects on economic growth in both the short and long run.…”
Section: Discussion Of Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…These findings corroborate the debt overhang hypothesis that an indebted country will find it difficult to undertake future investment projects since returns from any future investment would be diverted to the creditor in the form of promised payments (debt servicing) thereby creating a disincentive to invest and hence poor growth and development. The results of this study are also in tandem with the findings of previous empirical studies (Adubofour Isaac et al, 2021;Asteriou et al, 2021;Bal & Rath, 2014;Fejzaj et al, 2021;Fosu, 1996;Law et al, 2021;Le & Phan, 2022;Maitra, 2019;Makun, 2021;Manasseh et al, 2022;Pegkas, 2018) in which external debt stock and total external debt services were found to have significant adverse effects on economic growth in both the short and long run.…”
Section: Discussion Of Resultssupporting
confidence: 88%
“…Previous studies such as : (Bourne, 1983;Frimpong & Oteng-Abayie, 2006;Owusu-Nantwi & Erickson, 2016;Schclarek & Alfredo, 2004;Siddique et al, 2016) have found that external debt significantly stimulates economic growth. In contrast, (Adubofour Isaac et al, 2021;Asteriou et al, 2021;Bal & Rath, 2014;Fejzaj et al, 2021;Fosu, 1996;Law et al, 2021;Le & Phan, 2022;Maitra, 2019;Makun, 2021;Manasseh et al, 2022;Pegkas, 2018) have also shown that external debt has adverse repercussion on economic growth and developing, in most especially developing countries.…”
Section: Relationship Between External Debt and Economic Growthmentioning
confidence: 99%
“…The external debt of some countries, such as Senegal and Cote D'Ivoire, is expected to grow by more than 10% in the coming years (Nsonwu, 2022). Many African countries have experienced negative effects of debt burdens on their long-term economic growth, such as lower GDP growth, reduced investment and capital formation, and higher taxes to generate more revenue to repay the debts (Manasseh et al, 2022). Recent studies on debt sustainability by the IMF and the Ministry of Finance indicate that Uganda's debt is sustainable at present, but there is a slight possibility that it will become unsustainable in the medium and long term (Mageto, 2022).…”
Section: Primary Balance and Debt Sustainabilitymentioning
confidence: 99%
“…According to the International Labour Organization (ILO), Sub-Saharan Africa's massive debt burden is a major impediment to job creation and growth because investment resources that should be employed for productive purposes are diverted to fulfill external debt service commitments (Manasseh et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in external debt stock is being driven by an enormous increase in foreign debt, according to the Central Bank of Nigeria. Increased public spending, particularly on capital projects, loans from the international community at non-concessional interest rates, and an over-reliance on imports, which leads to trade arrears, are all considered major causes of Nigeria's debt situation while rising interest rate movements influenced the size of the external debt stock (Manasseh et al, 2022).…”
Section: Introductionmentioning
confidence: 99%